2017
DOI: 10.1007/s00586-017-4996-8
|View full text |Cite
|
Sign up to set email alerts
|

Painful Schmorl’s nodes treated by discography and discoblock

Abstract: Painful SNs refractory to medical or physical therapy should be an indication for treatment with discography and discoblock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…SNs could cause chronic back pain through inflammatory mediators and cytokines, which are produced by degenerative disc (annulus rupture) and osteonecrosis of the endplate [ 26 ]. Pathophysiological mechanisms of painful SNs are identified with the degenerative disc diseases, resulting in a special type of discogenic back pain, in which provocative discography is typically positive and spinal MRI shows a low signal intensity on T1WI, and a high signal intensity on T2WI (Mordic-I change), indicating degenerative changes of the disc material [ 25 ]. Surgical procedures including spinal fusion and discoblock can be used to manage this type of painful SN [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNs could cause chronic back pain through inflammatory mediators and cytokines, which are produced by degenerative disc (annulus rupture) and osteonecrosis of the endplate [ 26 ]. Pathophysiological mechanisms of painful SNs are identified with the degenerative disc diseases, resulting in a special type of discogenic back pain, in which provocative discography is typically positive and spinal MRI shows a low signal intensity on T1WI, and a high signal intensity on T2WI (Mordic-I change), indicating degenerative changes of the disc material [ 25 ]. Surgical procedures including spinal fusion and discoblock can be used to manage this type of painful SN [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hasegawa et al [ 23 ] presented a typical case of the eradications of intervertebral nucleus pulposus containing a SN and posterior lumbar interbody fusions to solve the symptomatic SN. Several other treatment methods, such as ramus communicans nerve blockade, discography, and discoblock have been proposed for the management of back pain secondary to suspected symptomatic SNs [ 8 , 24 ]. These techniques can provide rapid and lasting symptom relief.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with symptomatic SNs may have pain on manual compression and percussion of the vertebra similar to that of a traumatic vertebral compression fracture [ 6 ]. Symptomatic SNs are much less frequently identified on routine images than are their asymptomatic counterparts, and they have been described in the literature only in isolated case reports [ 7 , 8 ]. Some research has indicated that these symptomatic SNs might either respond to conservative therapies such as analgesics, bed rests, and external bracings, or heal spontaneously in most instances.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study of 223 patients with chronic LBP who underwent fluoroscopically guided lumbar discography and received intradiscal antibiotics prior to the procedure, no infections were recorded (16). Similarly, in a case series of 46 patients who underwent lumbar discography under fluoroscopic guidance to treat LBP caused by Schmorl nodes, no infections were reported within 1 year postprocedure (17).…”
Section: Discographymentioning
confidence: 99%